2014
DOI: 10.1002/brb3.212
|View full text |Cite
|
Sign up to set email alerts
|

Brain microstructural changes and cognitive correlates in patients with pure obsessive compulsive disorder

Abstract: ObjectThe aim of this study was to investigate macrostructural and microstructural brain changes in patients with pure obsessive compulsive disorder (OCD) and to examine the relationship between brain structure and neuropsychological deficits.Method20 patients with OCD underwent a comprehensive neuropsychological battery. A combined voxel-based morphometry (VBM) and diffusion tensor imaging (DTI) analysis was used to capture gray matter (GM) and white matter changes in OCD patients as compared to pair-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 111 publications
(219 reference statements)
4
32
1
Order By: Relevance
“…These functions are consistent with the impairments in perception of and attention to emotional information in ED, including prosody and facial expressions of emotion. Our findings of reduced FA in the SLF are also supported by the TBSS studies reported in the Supplement, including findings from studies of reduced FA in the left SLF in OCD (Spalletta et al, 2014) and PTSD (Fani et al, 2012), as well of studies of BD (Ambrosi et al, 2013), particularly in the left SLF (Versace et al, 2010), as well as in the right hemisphere in MDD (Murphy et al, 2012) and OCD (Benedetti et al, 2013), and bilaterally in treatment-resistant depression (de Diego-Adelino et al, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…These functions are consistent with the impairments in perception of and attention to emotional information in ED, including prosody and facial expressions of emotion. Our findings of reduced FA in the SLF are also supported by the TBSS studies reported in the Supplement, including findings from studies of reduced FA in the left SLF in OCD (Spalletta et al, 2014) and PTSD (Fani et al, 2012), as well of studies of BD (Ambrosi et al, 2013), particularly in the left SLF (Versace et al, 2010), as well as in the right hemisphere in MDD (Murphy et al, 2012) and OCD (Benedetti et al, 2013), and bilaterally in treatment-resistant depression (de Diego-Adelino et al, 2014). …”
Section: Discussionsupporting
confidence: 88%
“…Ascending fibers connect the thalamus to cerebral cortex, and descending fibers connect the fronto-parietal cortex to sub-cortical basal ganglia regions and the spinal cord (Catani et al, 2002). A key region in processing sensory and motor information, the corona radiata has also been reported to be heavily involved in cognitive control (Chaddock-Heyman et al, 2013;Mackiewicz Seghete et al, 2013;Spalletta et al, 2014) and motor regulation processes (Kim and Pope, 2005). In particular, a recent study reported impaired executive function performances in trail-making test in patients with damage to the posterior corona radiata region (Li et al, 2014).…”
Section: Posterior Corona Radiatamentioning
confidence: 97%
“…Of these, 16 articles reported foci that corresponded to increase or reduced FA in patients compared to controls (Admon et al, 2012;Benedetti et al, 2013;Fan et al, 2012;Garibotto et al, 2010;Gruner et al, 2012;Ha et al, 2009;Li et al, 2011Li et al, , 2013Lochner et al, 2012;Menzies et al, 2008b;Nakamae et al, 2008Nakamae et al, , 2011Spalletta et al, 2014;Szeszko et al, 2005;Yoo et al, 2007;Zarei et al, 2011). Out of the 16 articles, 6 were further excluded (4 utilized TBSS techniques, 1 utilized data-driven approach, 1 utilized ROIonly analyses), resulting in a final count of 10 articles for Study 3.…”
Section: Study 3: White Matter Famentioning
confidence: 97%
“…Of these, eight (8 datasets) consisted of OCD-youth samples (Carmona et al, 2007;Koprivova et al, 2009;Matsumoto et al, 2010b;Pujol et al, 2004;Riffkin et al, 2005;Spalletta et al, 2014;Subira et al, 2013;Tan et al, 2013;Tang et al, 2013;Togao et al, 2010;Valente et al, 2005;van den Heuvel et al, 2009;Yoo et al, 2008).…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
“…Of these, 30 VBM studies (including 3 negative studies) (Lazaro et al, 2014;Riffkin et al, 2005;Spalletta et al, 2014) were selected for further consideration after primary screening. No additional articles were found in the reference lists of the selected studies.…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%